The Artificial Intelligence-related Superordinate Concepts and Terminological Variation in the English and Ukrainian Languages - Mikelionienė, Jurgita; Ponomarevskyi, Artemii (Slavistica Vilnensis, 2024)
This research is aimed at analyzing the artificial intelligence-related superordinate concepts in the English and Ukrainian languages and explaining the relevance of using terminological variations from the field of artificial intelligence (AI) in a particular context on the example of translation from English (EN) into Ukrainian (UK). The essence of terminological variation as a linguistic phenomenon and possible reasons for its emergence are described. Terminological variants in the newly established field of artificial intelligence appear either in both EN and UK, or in one of those due to a specific understanding of objects and ideas in a particular language. The main concepts in EN and UK, which may include both terms and variants, in the field of AI are identified. On the example of building a basic concept model with the respect to the core concept of AI, the differences in understanding similar concepts in the EN and UK are explained.  Considering these differences, the contextually motivated ways of using the artificial intelligence-related terms or terminological variants in the examples of translation from EN into UK are provided.
Keywords: artificial intelligence-related concept model; superordinate concept; artificial intelligence-related terms; terminological variations; translation